In silico study of anti-inflammatory activity among new 2-((5-(2-bromo-5-methoxyphenyl)-4-r-1,2,4-triazol-3-yl)thio)acetic acids and their esters - Skoryi, M. P.; Al Halaf, N. A.; Аль Халаф, Наталія Анатоліївна (Запорізький державний медико-фармацевтичний університет, 2024)
The aim of the study. To investigate the anti-inflammatory activity of new 2-((5-(2-bromo-5-methoxyphenyl)-4-R-1,2,4-triazol-3-yl)thio)acetic acids and their esters using molecular docking.
Keywords: тези доповідей